Clinical drug interactions between voriconazole and 38 other drugs: a retrospective analysis of adverse events - Huo, Ben-Nian; Shu, Ling; Xiao, Jian-Wen; Yin, Nan-Ge; Ai, Mao-Lin; Jia, Yun-Tao; Song, Lin (Frontiers in Pharmacology, 2024)
Background: The primary goal of this study was to analyse the potential risk factors for AEs caused by DDIs between VRZ and other drugs via the OpenVigil FDA platform and provide a reference for preventing VRZ DDIs and monitoring clinically related adverse drug events.Methods: A retrospective pharmacovigilance study was conducted to investigate the AEs related to DDIs between VRZ and four categories of drugs, including proton pump inhibitors (PPIs), nonsteroidal anti-inflammatory drugs (NSAIDs), immunosuppressants and other antibacterial drugs.AE information for the target drugs from the first quarter of 2004 to the third quarter of 2022 was downloaded from the OpenVigil FDA data platform. Reporting ratio method, Ω shrinkage measure model, combination risk ratio model and chi-square statistics model were used to analyse the AEs related to DDIs and evaluate the correlation and influence of sex and age between the drug(s) and the target AEs detected.Results: 38 drugs were included. 262 AEs were detected by at least one of the four models, and 48 AEs were detected by all four models. 77 detected AEs were significantly positively correlated with DDIs and were related to higher reporting rates of AEs than when used alone. Graft-versus-host disease was the AE that had the strongest correlation with the drug interaction between VRZ and immunosuppressants, and multiple organ dysfunction syndrome was correlated with VRZ in combination with other antibacterial drugs. Significant sex and age differences in target AEs were detected for 5 and 9 target drugs, respectively. When conditions are aggravated, febrile neutropenia and septic shock should be of particular concern in patients over 18 years who use VRZ is combination with ceftazidime, ciprofloxacin or cytarabine. In patients under 18 years, septic shock should be considered when VRZ is used in combination with meropenem and dexamethasone.AEs related to DDIs should receive more attention when VRZ is used in combination with PPIs (i.e., renal impairment), NSAIDs (i.e., constipation and renal failure), immunosuppressants (i.e., graft versus host disease, septic shock) and other antibacterial drugs (i.e., multiple organ dysfunction syndrome, febrile neutropenia, and respiratory failure). Need to consider the influence of sex and age differences in VRZ DDIs